World-Famous Nine - Guterson, Ben; Kister, Kristina (New York Little, Brown and Company, 2024)
Eleven-year-old Zander is determined to save his grandmother's nineteen-story out-of-this-world department store from an evil force.
113103
Keywords: Department stores -- Juvenile fiction; Magic -- Juvenile fiction; Mystery and detective stories; Novels